Acacia angustissima intoxication of Menz lambs requires two components - Brown, D.L.; Yimegnuhal, A.; McCrabb, G.J. (2005)
This study sought to determine if sheep suffer neurological symptoms when fed Acacia angustissima leaves, and whether an equivalent amount of 70% acetone extract would have the same effect. In addition, the study tried to determine if treatment of leaves with 70% acetone would destroy the activity of A. angustissima toxins, and whether extraction with 70% aqueous acetone extract would separate two components of a toxic system. Twenty-five Menz lambs were randomly assigned to one of five treatments (1) A angustissima leaves as half the diet, 2) dried extract (70% aqueous acetone) of the same quantity of leaves, 3) a corresponding amount of residues, 4) a recombination of the dried extract and dried residue, or (5) a control diet containing no A angustissima leaves or extract fractions. All animals fed the leaves and the recombined fractions died or were euthanized when they were observed to be dying of severe neurological derangement. None of the other animals showed any neurological signs of impairement. The results of this study indicate that healthy, well-fed sheep can be poisoned by A angustissima, that the toxins are not destroyed by acetone or oven drying, and that severe neurological intoxication requires two components, which can be separated by acetone extraction.